Maullinia ectocarpii gen. et sp. nov. (Plasmodiophorea), an intracellular parasite in Ectocarpus siliculosus (Ectocarpales, Phaeophyceae) and other filamentous Brown algae. - Maier, Ingo (2000)
An obligate intracellular parasite infecting Ectocarpus spp. and other filamentous marine brown algae is described. The pathogen forms an unwalled multinucleate syncytium (plasmodium) within the host cell cytoplasm and causes hypertrophy. Cruciform nuclear divisions occur during early de- velopment. Mature plasmodia become transformed into single sporangia, filling the host cell com- pletely, and then cleave into several hundred spores. The spores are motile with two unequal, whiplash-type flagella inserted subapically and also show amoeboid movement. Upon settlement, cysts with chitinous walls are formed. Infection of host cells is accomplished by means of an adheso- rium and a stachel apparatus penetrating the host cell wall, and injection of the cyst content into the host cell cytoplasm. The parasite is characterized by features specific for the plasmodiophorids and is described as a new genus and species, Maullinia ectocarpii.